The Development of Electronic Students' Worksheet Assisted by Flip PDF Professional in Natural Science Lessons to Improve Students' Higher Order Thinking Skills - Farah Alya Gaurisankar; Sri Wahyuni; Ulin Nuha (Universitas Muhammadiyah Sidoarjo, 2022)
The development of electronic students’ worksheet assisted by flip PDF professional is used to develop students' HOTS in science lessons. The purpose of this research is to develop a valid, practical, and effective electronic students’ worksheet assisted by flip PDF professionals. The research method used is ADDIE model development research starting from the analyze, design, develop, implement, and evaluate stages. Data analysis techniques used in the study include validity, practicality, and effectiveness. Based on the results of data analysis obtained from several validators, it shows that the developed electronic students’ worksheet obtained an average percentage score of 93% with a very valid and good category to use. The results of practicality in the use of electronic students’ worksheet when learning obtained a percentage of 88.7% with a good category. In knowing the increase in students' HOTS, the N-Gain test was carried out and obtained a value of 0.65 with moderate criteria, which means that the electronic students’ worksheet assisted by flip PDF professionals is quite effective in increasing students' HOTS. The results of student responses to the use of the developed electronic students’ worksheet showed an average percentage score of 58.94%. Based on the analysis results obtained, the electronic students’ worksheet assisted by flip PDF professionals in science lessons to improve students' higher order thinking skills is feasible to use.